Helichrysum monizii Lowe: phenolic composition and antioxidant potential - Gouveia, Sandra (2012)
Introduction – In Madeira Archipelago there are four endemic Helichyrsum species and three of them are used in the traditional medicine. Helichrysum monizii is a rare endemism with very scarce information available concerning its uses in the local traditional medicine. Objective – The aim of this work was to study for the first time Helichrysum monizii in terms of its antioxidant capacity and the identification of the phenolic compounds to which that activity is due. Methodology – Three different methods of extraction were performed and total phenolic and flavonoid contents of extracts were correlated to radical scavenging and antioxidant capacity by DPPH, ABTS, FRAP and β‐carotene assays. An HPLC‐DAD‐ESI/MSn method was employed for the separation and identification of the phenolic and flavonoid components. Results – The results revealed a high antioxidant potential mainly related to the phenolic profile of the plant. Polar components of methanol extracts of Helichrsyum monizii were detected by a high‐performance liquid chromatography/ electrospray ionisation tandem mass spectrometry (HPLC‐DAD‐ESI/MSn ) method. Thirty‐three compounds were identified and 19 of them were identified as quinic acid derivatives.